In Visible Movement : Nuyorican Poetry from the Sixties to Slam - Noel, Urayoán (Book collections on Project MUSE., 2014)
Since the 1960s, Nuyorican poets have explored and performed Puerto Rican identity both on and off the page. Emerging within and alongside the civil rights movements of the 1960s, the foundational Nuyorican writers sought to counter the ethnic/racial and institutional invisibility of New York City Puerto Ricans by documenting the reality of their communities in innovative and sometimes challenging ways. Since then, Nuyorican poetry has entered the U.S. Latino literary canon and has gained prominence in light of the spoken-word revival of the past two decades, a movement spearheaded by the.